An Assessment of the Potential of Laser-Induced Breakdown Spectroscopy (LIBS) for the Analysis of Cesium in Liquid Samples of Biological Origin. Issue 7 (July 2014) - Metzinger, Anikó; Kovács-Széles, Éva; Almási, István; Galbács, Gábor
The present study describes the development of an analytical method for the determination of cesium in biological fluid samples (human urine and blood samples) by laser-induced breakdown spectroscopy (LIBS). The developed method is based on sample presentation by liquid-to-solid conversion, enhancing the emission signal by drying the liquid into small "pockets" created in a metal support (zinc plate), and allows the analysis to be carried out on as little as 1 μL of sample volume, in a closed sample cell. Absolute detection limits on the Cs I 852.1 nm spectral line were calculated by the IUPAC 3σ method to be 6 ng in the urine sample and 27 ng in the blood serum sample. It is estimated that LIBS may be used to detect highly elevated concentration levels of Cs in fluid samples taken from people potentially exposed to surges of Cs from non-natural sources.